Price transmission behaviour of major seed spices in Rajasthan: Price behaviour of seed spices in Rajasthan - Bairwa, Kailash Chand; Meena, G L; Singh, Hari; Balai, Harkesh Kumar; Yadav, Anju; Meena, P C (Journal of Spices and Aromatic Crops, 2023)
The present study was based on secondary price information. The study period from January, 2011 to December 2021 was chosen to analyse the price behaviour of major seed spice markets in Rajasthan. The data was analysed using the Augmented Dickey Fuller (ADF) test and Vector Error Correction Model to accomplish the objectives of the study. ADF test results showed that price data for coriander, cumin, fenugreek, and fennel were non-stationary at the level and stationary at the first difference level. Values of trace and maximum Eigen of Johansen multiple co-integration tests revealed three co-integration equations in cumin and coriander crops, but only one co-integration equation in fennel prices. Prices of coriander, cumin, and fennel in selected KUMS (Krishi Upaj Mandi Samiti) were primarily influenced by the one-month and two-month lag prices of respective market in the long run. The prices of coriander, cumin and fennel demonstrated one-way co-integration in KUMS, Merta City→KUMS, Jodhpur and Ramganj Mandi→Baran while combination of Baran↔Kota, Ramganj Mandi↔Kota and Merta City↔Niwai showed bi-directional co-integration. Fenugreek prices in selected KUMS did not move in tandem over a long period of time. We find that the prices of coriander, cumin and fennel in Rajasthan’s selected markets moved in lockstep over time and were influenced by one month or two months lag price of other respective markets.